2019
DOI: 10.1111/jfbc.12815
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic analysis and erectogenic function of African Walnut ( Tetracarpidium conophorum ) seeds: The impact of the seed shell on biological activity

Abstract: This study investigated the erectogenic potential of African walnut seed (AWS). The extract from AWS cooked with/without shell interacted with phosphodiesterase‐5 (PDE‐5), arginase, angiotensin‐I converting enzymes (ACE), and acetylcholinesterase (AChE); enzymes associated with erectile dysfunction (ED) and Fe2+‐induced malonaldehyde (MDA) production in the isolated penile tissue. The results showed that the extracts inhibited the enzymes and MDA production, but Walnut cooked with shell had the highest effect.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Although treatment with ACA alone cause a reduction of these enzymes, but mush reduced activities were observed in those that were co‐treated with the inclusive diets plus ACA, most especially those of ACA + 4% ML/MS inclusive diets. The noticed reversed in the activities of AChE, ACE, MAO, and ADA in the penile tissue of treated diabetic (Figure 4) can be ascribed to the effectiveness of the phenolic acids and flavonoids (Adefegha, Oyeleye, Dada, et al, 2018; Ademiluyi, Ogunsuyi, Adebayo, & Oboh, 2018; Ademiluyi et al., 2019; Ademosun & Oboh, 2017; Li, Nakagome, Hirono, Itoh, & Fujiwara, 2015).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Although treatment with ACA alone cause a reduction of these enzymes, but mush reduced activities were observed in those that were co‐treated with the inclusive diets plus ACA, most especially those of ACA + 4% ML/MS inclusive diets. The noticed reversed in the activities of AChE, ACE, MAO, and ADA in the penile tissue of treated diabetic (Figure 4) can be ascribed to the effectiveness of the phenolic acids and flavonoids (Adefegha, Oyeleye, Dada, et al, 2018; Ademiluyi, Ogunsuyi, Adebayo, & Oboh, 2018; Ademiluyi et al., 2019; Ademosun & Oboh, 2017; Li, Nakagome, Hirono, Itoh, & Fujiwara, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, the report of Adefegha, Oyeleye, Dada, Olasehinde, and Oboh (2018), showed that flavonoids such as quercetin and its glycosylated form (rutin) have the potential to reduced PDE-5 and arginase activities. Several lines of research have shown that inhibition of PDE-5 alone is not enough in the management of ED, not even to talk about the side effects exhibited by PDE-5 synthetic inhibitors (Adebayo, Oboh, & Ademosun, 2019;Ademiluyi et al, 2019). However, other enzymes such as AChE, ACE, MAO, and ADA, among others, which, if unchecked, could also wreak havoc toward sustaining ED, via the reduction of concentration of some vital biomolecules including NO, angiotensin-I, cGMP, and adenosine in the penile tissue (Adefegha, Oyeleye, Dada, et al, 2018;Jung, Jo, Kwon, & Jeong, 2014;Naylor, 1998;Phatarpekar, Wen, & Xia, 2010), most especially in diabetic subjects (Adebayo et al, 2019;Han et al, 2019;Yang et al, 2009).…”
Section: Discussionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dried and pulverized plant sample was subjected to aqueous (w/v) extraction (Ademiluyi et al., 2019). Filtered using Whatman No.1 filter paper, thereafter, the filtrates were freeze‐dried.…”
Section: Methodsmentioning
confidence: 99%
“…The use of Cyclosporine A (CsA) to suppress the immune system and autoimmune, so as to forbid incidence of organ rejection during organ transplant is highly practice (Agunloye et al., 2019; Huai et al, 2002). However, several side effects, including unchecked upregulation of rennin angiotensin system (RAS), angiotensin‐I enzyme (ACE) activity, and angiotensin‐1 receptor, reduce endothelia nitric oxide synthase (eNOS) activity and oxidative stress via increase production of radical species; the factors that are largely responsible for hypertension (Agunloye et al., 2019; Jabir et al., 2017; Oboh et al., 2016), erectile dysfunction (Adefegha, Oyeleye, Dada, Olasehinde, & Oboh, 2018; Ademiluyi, Oyeleye, Ogunsuyi, & Oboh, 2019), cognitive impairment (Tota et al., 2012), nephrotoxicity (Bekpinar et al., 2019), among others, have been reported. Interestingly, consumption of phenolic‐rich foods/plants have been reported to have good advantages toward the alleviation of these side effects and in the management of hypertension and cardiotoxicity (Agunloye et al., 2019; Bekpinar et al., 2019; Bingul, Olgac, Bekpinar, & Uysal, 2019; Josiah, Oyeleye, Crown, & Olaleye, 2020).…”
Section: Introductionmentioning
confidence: 99%